Volume-outcome relationship in transcatheter aortic valve implantations in Germany 2008-2014: a secondary data analysis of electronic health records - Kaier, Klaus; Oettinger, Vera; Reinecke, Holger; Schmoor, Claudia; Frankenstein, Lutz; Vach, Werner; Hehn, Philip; Zur Mühlen, Constantin von; Bode, Christoph; Zehender, Manfred Karl-Heinz; Reinöhl, Jochen (BMJ open, 2018)
We examine the volume-outcome relationship in isolated transcatheter aortic valve implantations (TAVI). Our interest was whether the volume-outcome relationship for TAVI exists on the centre level, whether it occurs equally for different outcomes and how it develops over time.
Gesehen am 15.04.2020